Integrating Human Rights Education to Combat Bullying in Schools: A Cross-Cultural Study - Agus Bambang Nugraha; Eny Kusdarini; Suharno Suharno; Berkah Adityo Szauli Putra (Dinasti Publisher, 2025)
Human rights education (HRE) has been shown to be an effective tool in combating bullying in schools. This study aims to explore the integration of HRE into school curricula across cultures and its impact on bullying behavior. Through case studies in several countries, including Indonesia, the United States, and Finland, the study found that a human rights-based approach not only increases students’ awareness of their rights and those of others, but also creates a safer and more inclusive school environment. The results of the study demonstrate the importance of cross-cultural collaboration in formulating effective strategies to reduce bullying in schools.